Carbon-Responsive Computing: Changing the Nexus between Energy and Computing - Dawn Nafus (MDPI AG, 2021)
While extensive research has gone into demand response techniques in data centers, the energy consumed in edge computing systems and in network data transmission remains a significant part of the computing industry’s carbon footprint. The industry also has not fully leveraged the parallel trend of decentralized renewable energy generation, which creates new areas of opportunity for innovation in combined energy and computing systems. Through an interdisciplinary sociotechnical discussion of current energy, computer science and social studies of science and technology (STS) literature, we argue that a more comprehensive set of carbon response techniques needs to be developed that span the continuum of data centers, from the back-end cloud to the network edge. Such techniques need to address the combined needs of decentralized energy and computing systems, alongside the social power dynamics those combinations entail. We call this more comprehensive range “carbon-responsive computing,” and underscore that this continuum constitutes the beginnings of an interconnected infrastructure, elements of which are data-intensive and require the integration of social science disciplines to adequately address problems of inequality, governance, transparency, and definitions of “necessary” tasks in a climate crisis.